Perubahan perilaku belajar melalui penggunaan media komik Pada Siswa Sekolah Dasar - Ginanjar, Sunandie Eko; Sutinah, Sutinah; Jatmiko, Ginanjar Agung; Hermawan, Hari (Universitas Muhammadiyah Magelang, 2023)
Education is a facility in improving the ability to meet various needs. Education in Indonesia has formal, informal, and non-formal education. The research conducted focused on formal education, namely elementary school education. Basic education is the basis of education that is the foundation for students in pursuing higher formal education. Students at the elementary school education level are the stages of child development who still need concrete objects or at the concrete operational stage. This stage is more about learning that uses concrete or real objects, so that students will get meaningful learning. Learning at the concrete operational stage requires a medium that facilitates learners in learning, especially in the use of image-space or visual-spatial intelligence. This intelligence can be built through learning that uses pictorial media and has meaning. If the media used is not suitable, there will be problems or problems planned. The research conducted will determine changes in behavior when learning to use comics at SDN Nagrog, Bandung Regency.. The research method carried out is to use the Class Action Research (PTK) method with the Elliot model which has several implementation cycles. The resulting research results are that there are changes in the level of student practice seen from the learning outcomes of cycle I, cycle II, and cycle III. Each stage has an improved level of learning outcomes, and conducive and active classroom conditions. Therefore, the regular use of comics on materials in elementary grades is very effective in changing the behavior of learners, so learning outcomes will improve. Keywords: concrete operations, behavior change, comic media